In vitro free radical scavenging and thrombolytic activities of Bangladeshi aquatic plant Aponogeton undulatus Roxb - Chowdhury, Nargis S; Alam, Md. Badrul; Haque, A S M Tanbirul; Zahan, Ronok; Ehsanul, M; Mazumder, Haque; Haque, M Ekramul (© IDOSI Publications, 2011, 2016)
This article was published in Global Journal of Pharmacology [© IDOSI Publications, 2011] and the definite version is available at: https://idosi.org/gjp/5(1)11/6.pdf